Multiphase flow simulations and experiments on electrochemical jet machining of rough surfaces of high-speed additive manufactured titanium alloys - Yang Liu; Xinyu Liu; Jinzhong Lu; Zhaoyang Zhang; Kaiyu Luo; Shu Huang; Haifei Lu; Gang Xu; Guoqing Dai; Siyu Zhou (Virtual and Physical Prototyping)
The application of titanium alloy parts manufactured by high-speed additive manufacturing in industry is currently constrained by the low surface accuracy. This severely constrains the potential of high-speed additive manufacturing for processing aerospace titanium alloy components. To address this issue, it is crucial to address the high-speed additive manufactured rough surface in order to enhance surface accuracy. As a highly flexible non-contact machining method, electrochemical jet machining is well-suited for surface post-treatment of additive manufactured titanium alloy parts due to its distinctive advantages, including the absence of tool loss, no cutting force, and no thermal effects. This paper examines the electrochemical jet machining of rough low-precision surfaces produced by high-speed additive manufacturing. The distribution characteristics of the machining electric field and machining flow field on extremely rough additive manufactured surfaces were investigated through simulation. A series of experiments were conducted to verify the effectiveness of the simulation. The research findings indicated that the cut-in electrochemical jet machining method effectively circumvented the adverse effects of rough surfaces on electrolyte flow, thereby allowing for high-quality machining. The surface roughness of titanium alloy samples produced by high-speed additive manufacturing was reduced from Ra 21.179–1.838 um, representing a 90% reduction.